Intra-vaginal use of misoprostol for induction of labour in intrauterine death. - Easmin, S; Nahar, K; Jahan, MK; Rahim, R; Nila, TA; Nigar, K; Khan, NA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):566-9 The abstract of this article is available on the PubMed website